An Appraisal of the Practice of Sufism and Jalabi among Yoruba Muslims in Nigeria - Dauda Gambari Yusuph; Oniye Olayinka Ibrahim (Research Synergy Foundation, 2023)
Jalabi and Sufism are two abiding practices among Yoruba Muslims. Both have been instrumental to the consolidation and propagation of Islam across the Yorubaland. Many early Yoruba Muslims, especially the Islamic scholars, were both Jalabi practitioners and Sufi adherents. Many Muslims of later generations have, however, abused both. Hence, the coming of Salafiyyah advocates to displace the two, having been considered as innovations (bidcah) that endure among the Muslims. The Salafiyyah advocates propelled another misconception as they failed to acknowledge the parallels between the two but tarred both with the same brush. This now makes it difficult to record the necessary corrections to purge society of the evils of quacks that parade themselves in the land under the guise of Islam. Therefore, This study aims to examine the two phenomena to find their legitimacy in Islam and identify the similarities or otherwise between them. It will also determine the appropriateness or otherwise of Salafiyyah's advocacy against them. Historical and exegetical methods are adopted. The former enables the assessment of historical facts connected to Jalabi and Sufism in Yorubaland. At the same time, the latter allows assessing relevant works, especially the primary sources of Islam, to find the legitimacy for the two variables of this paper. Findings revealed that Sufism came down to Yorubaland along with Islam and that early Muslim scholar devised Jalabi as a dacwah strategy to consolidate and propagate Islam in the land. It also revealed that both exist independently, though combined by some scholars, while many Jalabi practitioners are not Sufis and vice versa. The work concluded by recommending that Salafiyyah scholars address each according to its peculiarities because Jalabi practitioners in modern times are businessmen, while the Sufis are not.